ANALISA RT434A SEBAGAI PEMANCAR UNTUK REMOTE MONITORING LEVEL DAYA SPEAKER BERBASIS MIKROKONTROLLER - Ashari, M. Ibrahim; Setiawan, Rachmadi (DINAMIKA DOTCOM, 2019)
Radio Network already exist and it was used long time ago. Its use that the radio networks can communicate through frequency in the air, definitely it simplifies us to transmit the information to others. Along with the development of technology nowadays, the radio network has been applied into several media, one of the impact of an advanced technology is the existing of transmitter for remote of a level monitoring for speaker power based microcontroller. This study used Microcontroller ATmega 8535 as the voltage level processor in which produced by the speaker to be transformed into data and utilize the RF communication media with frequency drop of 433 MHz which used to transmit data to the speaker, so it can be displayed through the computer. The result of the establishment of this device, namely pin ADC on the MicroController has read the data analog from the speaker and pin TXD on MicroController has transmit the data well. Keywords : ADC, Microcontroller, RT434A